Pengembangan Alat Desalinasi Air Laut dengan Teknologi Thermal Energy Storage - Muhammad Abdul Munir; Reza Abdu Rahman; Dwi Rahmalina (Fakultas Teknik Universitas Pancasila, 2023)
The need for clean water in household life is very important because humans cannot live without it. The composition of seawater consists of 96.5% pure water and 3.5% other materials, namely salts, dissolved gases, and others. Indonesia is one of the countries that has the second-longest coastline in the world, so the potential for utilizing sea water is very large, one of which can be through the desalination process. Distillation itself is distillation, and its by-product is salt when seawater is heated using a heat energy source with a concentrated solar power (CSP) system. Based on research that has been done previously, the tool is a lab-scale seawater desalination device, but the process of making a lab-scale seawater desalination tool is not optimal. Then design the construction of a lab-scale seawater desalination device with the Multi Stage Flash (MSF) type, and the aim is to determine the performance and functionality of the MSF-type lab-scale seawater desalination device. The results show that the results of the coil heat exchanger development obtained an inlet temperature of 85.9°C and an outlet temperature of 67.8°C, and the room temperature in the chamber can be maintained at a temperature of 68.9°C. As for the components being developed, such as sea water pumps, hoses, tees, and sprayers, a sea water debit of 53.78 liters per hour has been obtained.